African independent church pneumatology and the salvation of all creation - Daneel, M. L. (International Review of Mission, 1993)
Focuses on the birth, proliferation and phenomenal growth of sub-Saharan African independent churches. Origin of churches through a variety of schismatic processes; Acceptance and application of scripture; Belief in a triune God; Pervasive presence of an indwelling Holy Spirit.
Paid
Keywords: INDEPENDENT churches; SUB-Saharan Africa